1997
DOI: 10.1002/(sici)1520-6327(1997)34:3<329::aid-arch7>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and metabolism of exogenous ecdysteroids in the egyptian cotton leafwormSpodoptera littoralis (lepidoptera: noctuidae)

Abstract: After ingestion of various amounts of either [3H]ecdysone or [3H]20‐hydroxyecdysone (0.8 ng to 10 μg) by sixth instar larvae of the Egyptian cotton leafworm Spodoptera littoralis, apolar metabolites are rapidly detected in the gut and frass. Hydrolysis of the apolar products with Helix hydrolases releases solely [3H]ecdysone or [3H]20‐hydroxyecdysone, respectively. This, coupled with the formation of chemical derivatives (acetonide and acetate) which cochromatograph with authentic reference compounds on hptlc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…In the haemolymph (Figure 8c) and carcass (Figure 8d), in addition to material co-chromatographing with 20E, two peaks were observed. Comparing these results to those obtained previously after injection of [ 3 H]20E into the haemolymphs of Spodoptera littoralis and Lacanobia oleracea (Blackford & Dinan, 1997a; Blackford et al, 1997), the peak eluting in fractions 3-4 is likely to represent 20-hydroxyecdysonoic acid and the peak eluting in fractions 13-14 is probably 20,26-dihydroxyecdysone. Similar peaks are observed in the gut contents ( Figure 8e) and frass ( Figure 8f) after injection, although the broad nature of the 20E peak suggests that this material may represent more than one compound.…”
Section: Metabolism Of Ingested and Injected [ 3 H]20hydroxyecdysonesupporting
confidence: 79%
See 2 more Smart Citations
“…In the haemolymph (Figure 8c) and carcass (Figure 8d), in addition to material co-chromatographing with 20E, two peaks were observed. Comparing these results to those obtained previously after injection of [ 3 H]20E into the haemolymphs of Spodoptera littoralis and Lacanobia oleracea (Blackford & Dinan, 1997a; Blackford et al, 1997), the peak eluting in fractions 3-4 is likely to represent 20-hydroxyecdysonoic acid and the peak eluting in fractions 13-14 is probably 20,26-dihydroxyecdysone. Similar peaks are observed in the gut contents ( Figure 8e) and frass ( Figure 8f) after injection, although the broad nature of the 20E peak suggests that this material may represent more than one compound.…”
Section: Metabolism Of Ingested and Injected [ 3 H]20hydroxyecdysonesupporting
confidence: 79%
“…This led to the suggestion that, where they occur in plants, they contribute to the deterrence of invertebrate predation (Galbraith & Horn, 1969). However, only a few insect species have been tested for their susceptiblity to ingested ecdysteroids and, of these, some are susceptible (Kubo et al, 1983;Arnault & Sláma, 1986;Tanaka & Takeda, 1993;Tanaka & Naya, 1995;Blackford & Dinan, 1997b) while others are unaffected even by very high concentrations (Robbins et al, 1968;Kubo et al, 1987;Robinson et al, 1987;Tanaka & Naya, 1995;Blackford et al, 1997). Thus, the developmental importance of ecdysteroids to insect development and their structural differences to vertebrate steroid hormones encourage the search for compounds which interfere with this hormonal system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of P. interpunctella, the detoxification mechanisms are more complex, as they involve both a dehydrogenase/epimerase reaction and 22acylation. The situation is similar in S. littoralis (Webb et al, 1995(Webb et al, , 1996Blackford et al, 1997). The lack of 3-epimerization in O. nubilalis was an unexpected finding, as such a reaction is widespread in lepidopteran larvae (Weirich and Bell, 1997;Lafont et al, 2005).…”
Section: Diversity Of Detoxification Pathways Against Ingested Ecdystmentioning
confidence: 77%
“…Some Helicoverpa species (Helicoverpa virescens and Helicoverpa zea) can tolerate high concentrations of 20E in their diet without any detrimental effects (Kubo et al, 1981). Blackford et al (1996Blackford et al ( , 1997 also found that exogenous application of 20E could not affect the normal growth and development of Spodoptera littoralis and Lacanobia oleracea (Blackford et al, 1996;Blackford and Dinan, 1997b). Furthermore, in those noctuid insects, the high resistance is mainly due to the effective conversion of the ingested ecdysteroids into 22-long-chain-fatty-acyl esters in the gut (Kubo et al, 1987;Robinson et al, 1987;Zhang and Kubo, 1993;Blackford et al, 1997).…”
Section: Introductionmentioning
confidence: 99%